Manual reduction in testicular torsion and subsequent treatment after successful reduction: a series of reports in a single institution - Qi, Xiaokang; Yu, Junjie; Ding, Xuefei; Wang, Yehua; Zhu, Haiyan (Frontiers in Pediatrics, 2024)
Introduction: To explore the factors affecting the success of testicular torsion manual reduction and the safety of subsequent conservative treatment after successful reduction.Methods: Clinical data of 66 patients with testicular torsion treated in our emergency department from February 2017 to February 2022 were retrospectively collected. Manual reduction without anesthesia was performed in 19 patients. Patients with successful manual reduction chose different subsequent treatments according to the wishes of themselves and their guardians, including continuing conservative treatment and surgical exploration. Relevant clinical data were collected and analyzed.Results: Manual reduction was successful in 11 patients (11/19). Seven of them chose to continue conservative treatment, and four underwent surgical exploration immediately. Among the 7 patients who were treated conservatively, 3 underwent surgical treatment due to scrotal discomfort or testicular torsion at different stages, and the remaining 4 patients showed no recurrence of torsion during follow-up. Compared with other patients, patients with successful manual reduction had the shorter duration of pain (p<0.05). The time from visiting our hospital to surgery in patients who attempted manual reduction was slightly shorter than those who underwent surgery directly (p>0.05). The testes of these 11 patients were all successfully preserved. Conclusions: The short duration of pain may contribute to the success of manual reduction, and manual reduction did not increase the preparation time before surgery. Due to the unpredictable risk of recurrence, immediate surgical treatment is still recommended，or postponed elective surgical treatment should be offered in the next days or weeks.